STUDI PENGAMATAN PERTUMBUHAN MISELIUM DAN PEMBENTUKAN PINHEAD JAMUR TIRAM PUTIH (Pleurotus ostreatus) PADA MEDIA SERASAH DAUN KAKAO (Theobroma cacao L.) DAN SERBUK GERGAJI - Tasnin Tasnin (Biocelebes, 2015)
This study aims to observe the growth of mycelium and pinhead formation of a white oyster mushroom (Pleurotus ostreatus) on cocoa leaf litter were added sawdust. The research was designed in a completely randomized design (CRD) consist of five treatments and three repetitions, following treatment arrangement P1 (80% cocoa leaf litter + 20% basic media), P2 (cocoa leaf litter 60% + media base 40%), P3 (cocoa leaf litter 40% + 60% basic media), P4 (20% cocoa leaf litter basic medium + 80%) and P5 (media base 100%). Parameter observation that mycelium growth until media in the baglog is full (day), and time (day) required pinhead formation 3 times in the same baglog. The results showed the treatment P5 (media base 100%) is the best medium for the growth mycelium and pinhead formation of white oyster mushroom (Pleurotus ostreatus). The mycelium can full in baglog for 32 days, followed by treatment (P4), (P3) and (P2) for 36 days, whereas treatment (P1) showed no growth of mycelium. Pinheand first formed on treatment (P5) 15 days after the mycelium already fully in the baglog, followed by treatment (P4 and P3) 20 days, and treatment (P2) for 21 days. Pinhead-II to the treatment (P5) formed on day 29, whereas (P4) on day 31, (P3) the 34th and (P2) days 43. Pinhead-III formed to treatment (P5) on the 49th day, (P4) day 50, (P3) the 55th, and (P2) on the 69th.Keywords : white oyster mushroom (Pleurotus ostreatus) leaf litter cocoa (Theobroma cacao L.) and sawdust.